2014
DOI: 10.1371/journal.pone.0088894
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Kallikrein Mediates Pro-Inflammatory Pathways and Activation of Protease-Activated Receptor-4 in Proximal Tubular Epithelial Cells

Abstract: Tissue kallikrein (KLK1) expression is up-regulated in human diabetic kidney tissue and induced by high glucose (HG) in human proximal tubular epithelial cells (PTEC). Since the kallikrein-kinin system (KKS) has been linked to cellular inflammatory process in many diseases, it is likely that KLK1 expression may mediate the inflammatory process during the development of diabetic nephropathy. In this study, we explored the role of KLK1 in tubular pro-inflammatory responses under the diabetic milieu. Recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 52 publications
(73 reference statements)
1
34
0
Order By: Relevance
“…29 Interestingly, immunoreactive PAR2, but not PAR1, was higher in biopsy specimens from patients with DN than in specimens from patients without DN. 30 These results support the importance of PAR2 in the pathogenesis of DN. Fondaparinux, a FXa inhibitor, is suggested to reduce DN in db/db mice.…”
Section: Discussionsupporting
confidence: 66%
“…29 Interestingly, immunoreactive PAR2, but not PAR1, was higher in biopsy specimens from patients with DN than in specimens from patients without DN. 30 These results support the importance of PAR2 in the pathogenesis of DN. Fondaparinux, a FXa inhibitor, is suggested to reduce DN in db/db mice.…”
Section: Discussionsupporting
confidence: 66%
“…albicans- infected IL-17RA -/- mice and in WT mice (Fig 2D). A previous study suggested that Klk1 may induce inflammatory cytokines in human RTECs, at least in vitro [37]. However, we found that overexpression of Klk1 had very little impact on renal inflammatory gene expression or fungal load (Fig 2E and S2D Fig).…”
Section: Resultsmentioning
confidence: 55%
“…Additionally, Klk1 activates protease-activated receptors (PAR) such as PAR4 to trigger the release of inflammatory mediators from RTEC [37]. To define the role of Bdkrb activation in renal immunity, IL-17RA -/- mice were treated with bradykinin (300 nmol/kg) and survival evaluated following infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate contradictory effects of elevated levels of KLK1 expression on diabetic nephropathy. KLK1 exhibits renoprotective effects [139], but can also mediate a pro-inflammatory pathway via Proteinase Activated Receptor (PAR) activation [140]. Despite extensive research aimed at better understanding the molecular basics of renal and cardiovascular diseases, the overall view of interplay between kallikreins and other functional proteins still is unclear.…”
Section: Physiological Function Of Klksmentioning
confidence: 99%